Global economic prospects 2004 realizing the development promise of the doha agenda - ebrary, Inc. (Washington, D.C. : World Bank, 2003)
The book analyzes the most critical multilateral trade issues and suggests policy options that would raise living standards in developing countries and reduce global poverty
osc 28/10/2021
Loans
Keywords: Free trade; Economic forecasting